Unmet need for family planning among Syrian migrant women living in Turkey and its determinants - Sema Cifci; Sibel Icke; Sevil Hakimi (BMC, 2024)
Abstract Introduction Migrant women might be cannot benefit from health services sufficiently. The unmet need for family planning is among the pivotal indicators for measuring progress toward improving maternal and child health. The aim of this study was to identify the unmet need for family planning (UMNFP) among Syrian migrant women living in Mardin and its determinants. Material and methods The study was conducted in Mardin. Data were gathered during home visits Data collection tools were socio-demographic and reproductive health questionnaires. The statistical analysis was performed using SPSS software. Qualitative variables were presented by number and percentage. Quantitative variables were presented by means (standard deviation). To determine, the determinants of UMNFP binary logistic regression was used. Results The result of this study showed that prevalence of UMNFP was 35%. Woman's low educational level (OR:5.42, CI95%:2.43-8.94), history of un intended pregnancy(OR:1.43, CI95%:1.1-1.94) and induced abortion (OR:1.76, CI95%: 1.41-2.21), not having husband's regular job(OR: 2.24, CI95%:1.92-3.78) and lack of woman`s autonomy in decision related to use of contraception methods(OR:3.21, CI95%: 1.78-6.12) were determinants of UMNFP. Conclusion The prevalence of UMNFP among Syrian immigrants living in Mardin was considerable. Understanding the challenges and the barriers impacting use of contraception including cultural norms as well, as social and language obstacles are essential to decrease UMNFP.